Fungsi Perum Perhutani Kesatuan Pemangkuan Hutan (KPH) Surakarta dalam Pengendalian Kebakaran Hutan di Kawasan Gunung Lawu - Ida Andira Martines; Fatma Ulfatun Najicha (Jurnal Discretie, 2020)
This research will answer the function of forest fire control in the Gunung Lawu area by Perum Perhutani KPH Surakarta. In this study normative legal research is used with a prescriptive nature. The approach is carried out with a statutory approach, legal materials are primary and secondary legal materials. Collection of legal materials by literature study or document study and interviews. The technique of analyzing legal materials uses the deductive syllogism method, which is to draw conclusions from general matters concerning the problems at hand. The function of Perum Perhutani KPH Surakarta in controlling forest fires in the Gunung Lawu area carries out 6 (six) functions including; Planning and Evaluation Functions, Infrastructure Preparation and Maintenance Functions, Logistics Preparation Functions, Coordination Functions, and Operational Functions. In its implementation, inconsistencies with statutory regulations were found, namely in the implementation of the Operational Function for post-forest fire handling. Inconsistencies in the application of the law can have implications for lawlessness.